Cutaneous T‐cell lymphoma – Sézary syndrome in a Boxer. (28th December 2015) - Rütgen, Barbara C.; Flickinger, Irene; Wolfesberger, Birgitt; Litschauer, Barbara; Fuchs‐Baumgartinger, Andrea; Hammer, Sabine E.; Saalmüller, Armin; Schwendenwein, Ilse
Abstract: A 7‐year‐old male Boxer with a 3.5‐year history of atopy and food hypersensitivity was presented with multiple poorly circumscribed nodules and maculae of the skin and tongue, and jaundiced mucosal membranes. Cytologic and histopathologic examination of the skin lesions revealed cutaneous epitheliotropic lymphoma. Cells were CD3 + and CD8 + in flow cytometry. The CBC showed a moderate leukocytosis with 16% atypical lymphocytes with irregularly cleaved nuclei. Flow cytometric phenotyping of peripheral blood showed an elevated proportion of the CD8 + T‐lymphocyte subpopulation, indicating a malignant population of T‐cell origin, and the electropherogram of the PCR antigen receptor rearrangement produced a monoclonal peak for TCRγ. Liver enzyme activities were markedly increased and abdominal ultrasound examination showed increased echogenicity of the liver and enlarged abdominal lymph nodes. Fine‐needle aspirates of the liver confirmed infiltration with lymphocytes exhibiting the same morphology as the cells detected in skin and peripheral blood. Treatment was induced with L‐asparaginase, lomustine, and prednisone. Partial clinical remission of the skin and tongue lesions was achieved within 10 days, and hematologic abnormalities resolved. Despite further treatment with L‐asparaginase and lomustine, the dog relapsed within one month and was euthanized. Presence of malignant lymphocytes in skin, peripheral blood, and liver indicate a rare variant of leukemic cutaneous T‐cell lymphoma, equivalent of Sézary syndrome in a dog. This case report describes the use of flow cytometry as a complementary tool for lymphocyte characterization of skin lesions for the first time.